Analisis Kinerja Perusahaan Sektor Semen di Indonesia Dengan Pendekatan Data Envelopment Analysis - Amirul Bahar; Ahmad Syaifullah (Advantage: Journal of Management and Business, 2026)
The cement industry is one of the strategic sectors that supports infrastructure development and national economic growth. Increasing competition and persistent oversupply issues require cement companies to maintain efficiency and performance in order to remain competitive in the market. This study employs the Data Envelopment Analysis (DEA) approach using the CCR (Constant Return to Scale) model to measure the relative efficiency levels of cement companies in Indonesia. Secondary data were obtained from financial reports, with input variables consisting of total assets, operating expenses, and the number of employees, while the output variable used was net income. The analysis results indicate variations in efficiency levels across companies. Some firms achieved an efficiency score of 1.000 (efficient), while others remained below the optimal efficiency standard. These findings highlight differences in resource utilization and operational performance among firms. This study also provides recommendations and improvement strategies to help companies achieve more efficient and optimal performance.